1986
DOI: 10.1037/0735-7044.100.4.512
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of morphine and immobilization stress on discrimination performance of rats.

Abstract: The effects of morphine and those of immobilization stress (IMS) on performance of rats in discrete-trial, two-choice discrimination tasks were compared. In Experiments 1 and 2, two shocks of different intensities were discriminative stimuli (SD) for choices in a T-maze. In Experiments 3 and 4, responses were right and left lever presses in an operant chamber, where correct responses were signaled by either shocks of different intensities (shock discrimination task) or by the position of a brief light flash (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Recent studies on the behavioral functions of endogenous opioid systems in rodents have led to the suggestion that opioid peptides may play a role in the regulation of attention. This suggestion is consistent with reports of opiate disruption of concentration in humans and discrimination task performance of animals (Hernandez and Appel 1979;Jaffe and Martin 1985;Grilly and Gowans 1986). Conversely, opioid antagonists such as naloxone and naltrexone have been found to augment behavioral and electrophysiological measures of attention and arousal in humans and rats (Gritz et al 1976;Burks and Dafny 1977; Offprint requests to: D. M. Grilly Arnsten and Segal 1979;Arnsten et al 1984).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Recent studies on the behavioral functions of endogenous opioid systems in rodents have led to the suggestion that opioid peptides may play a role in the regulation of attention. This suggestion is consistent with reports of opiate disruption of concentration in humans and discrimination task performance of animals (Hernandez and Appel 1979;Jaffe and Martin 1985;Grilly and Gowans 1986). Conversely, opioid antagonists such as naloxone and naltrexone have been found to augment behavioral and electrophysiological measures of attention and arousal in humans and rats (Gritz et al 1976;Burks and Dafny 1977; Offprint requests to: D. M. Grilly Arnsten and Segal 1979;Arnsten et al 1984).…”
supporting
confidence: 88%
“…Thus, we assumed that task accuracy was heavily dependent on the degree to which the animal attended to the cue and that any temporary enhancement in accurate choice performance induced by drugs would be due to alterations in attentional or motivational processes. As would be expected of a task in which performance is heavily related to attention (Dember and Warm 1979), accuracy in this task has been found to be inversely related to choice latency (Grilly and Gowans 1987) and to be directly related to cue duration (Grilly and Gowans 1986) and to the rats' orientation towards the cue lights at the time of onset (unpublished observations).…”
mentioning
confidence: 66%
“…Under a variety of conditions, my colleagues and I have found that low doses of several psychostimulant drugs can improve performance of nonfatigued, adult rats trained in a two-lever, discrete-trial stimulus detection procedure in which a brief cue light was presented in one of two randomly determined locations al the beginning of each trial to indicate which leverpress was rewarded. We have found improvements in performance (choice accuracy and response time [RT]) following low doses of nicotine (Grilly, Simon, & Levin, in press) and the indirect dopamine agonists al-amphetamine (Grilly & Gowans, 1988;Grilly et al, 1989;Grilly & Simon, 1994), cocaine (Grilly, 1992;Grilly et al, 1989;Grilly & Grogan, 1990;Grilly & Nocjar, 1990;Grilly & Pistell, 1997), and pemoline (Grilly, 1999), but not behaviorally relevant doses of morphine (Grilly & Gowans, 1986), opiate antagonists (Grilly & Gowans, 1986;Grilly & Gowans, 1988), the selective serotonin reuptake inhibitor fluoxetine (Grilly & Pistell, 1997), or the indirect serotonin-dopamine agonist 3,4-methylenedioxymethamphetamine (Grilly, unpublished observations).…”
mentioning
confidence: 99%
“…There is also considerable research that indicates that exposure to unsignaled shock classically conditions fear to contextual cues, which in turn disrupts operants maintained with positive reinforcement (Baker & Mercier, 1982;Randich & LoLordo, 1979). Although little attention has been paid to the effects of acute stressors on more complex learned behavior, a few studies have indicated that stressors such as immobilization (Grilly & Gowans, 1986) and multiple shock exposure (Rosellini et al, 1982) can disrupt accuracy in appetitive choice tasks.…”
Section: Discussionmentioning
confidence: 99%